Comparative Study of Two Thoracic Radiotherapy Schedules for Palliation of Symptom, Radiological Response and Acute Toxicities in Advanced Non-small Cell Lung Cancer - Bairwa, Subhash Chand; Gothwal, Ravinder Singh; Ram, Badri; Gupta, Shivani; Meena, Chetna (Asian Pacific Journal of Cancer Care, 2021)
Aim: To compare the effect of two RT schedules for thoracic palliation in advanced NSCLC patients (30 Gy in 10 fractions over two weeks and 27 Gy in 6 fractions over three weeks, 2 fractions per week) on pulmonary symptoms, radiological response of the primary thoracic tumour, pulmonary functions and acute toxicities. Material and method: A hospital based quantitative prospective follow-up study. Total 104 advanced NSCLC patients were randomized into two fractionation arms. Evaluation was done pretreatment and 4 weeks after end of RT. Symptoms palliation and radiological response to RT & radiation pneumonitis were assessed by using RTOG 4-point scale and Revised (RECIST) guideline version 1.1 respectively. Radiotherapy was given by Cobalt-60 teletherapy machine. Results: Total 96 patients were evaluated for symptom palliation, radiological response and acute toxicities. The percentage of patients achieving symptom palliation was slightly higher in the control arm. At 1st month of follow-up, 16.67% & 18.75% patients in Study & control arm showed PR. Post-RT mean FVC and FEV1 showed a tendency for improvement in both mean FVC and FEV1 in compare to baseline. Treatment was well tolerated both arms. Grade I nausea and vomiting developed in 43% and 37.5% patients in Study and Control Arm respectively. 58% & 39% patients developed Grade 1 radiation pneumonitis as cough & dyspnea in study and control arms respectively. Grade 2 radiation pneumonitis was developed in 2 patient of study arm at 3rd week of follow-up but they lost follow up. Around 31% patients developed Grade1 esophagitis as dysphagia in both arms at 1 week of follow-up which was reduced up to 7% by 2nd week. A very few patients developed grade1 skin reaction as dermatitis in 1st week of treatment. The difference in symptom palliation, radiological response, pulmonary functions and acute toxicities in both arms was not statistically significant. Conclusion: The two RT fractionation schedules showed equal efficacy in terms of symptoms palliation, radiological response of the primary thoracic tumor, pulmonary functions and acute toxicities. Thus the 27 Gy/6 fractionation arm appears preferable compared to 30 Gy/10 arm to minimize the patients’ visits and load on the machines.